Digital Literacy Practices of Elementary School Teachers: Praktik Literasi Digital Guru Sekolah Dasar - Anggraeni, Ratna Dwi; Wachidah, Kemil (Universitas Muhammadiyah Sidoarjo, 2025)
Background: Digital literacy has become a fundamental requirement for elementary school teachers as education increasingly integrates technology. Specific Background: Teachers are expected to utilize digital tools to facilitate learning, yet their actual abilities often vary widely. Gap: Limited studies have explored teachers’ digital literacy in the context of a single classroom and specific grade level. Aim: This study aims to analyze the digital literacy capabilities of a grade V teacher at Kandangan State Elementary School. Results: The findings show that the teacher demonstrates adequate competence across five dimensions of digital literacy: visual, reproduction, branching, information, and socio-emotional literacy. The teacher integrates digital media into lessons, uses technology to search and reproduce learning materials, and maintains communication with parents through digital platforms. Novelty: This research provides a focused case-based insight into teacher digital literacy within a real classroom environment. Implications: Schools need to strengthen digital literacy programs by providing better facilities and continuous training to support teachers in integrating technology effectively. Highlights• Digital literacy competencies of a grade V teacher• Integration of digital media into classroom practice• Identification of obstacles in digital implementation Keywords: Digital Literacy, Elementary Teacher, Online Resources, Digital Pedagogy, Classroom Practice